Penggunaan Metode Fonik untuk Meningkatkan Kemampuan Membaca pada Anak Slow Learner - Sholikhatun Nisa; Rudi Cahyono (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Reading proficiency is a fundamental skill in primary education; however, children with special needs classified as slow learners often face significant challenges in developing early reading abilities due to limitations in phonological processing. This study aims to examine the effectiveness of the phonic method in improving the reading skills of slow learners through a structured intervention approach. The central research problem addresses how the phonic method can be appropriately adapted to overcome reading difficulties in children with learning delays. The subject of this study was a fifth-grade elementary school student who exhibited marked delays in recognizing letter sounds, constructing words, and understanding simple sentence structures. A case study approach was employed, involving a six-session individualized intervention designed in gradual stages. Each session focused on developing phonological skills, including phoneme identification, blending sounds into syllables, phoneme segmentation, and the introduction of complex patterns such as digraphs and diphthongs. The results demonstrated significant improvement in the subject’s reading ability, evidenced by increased accuracy in letter-sound recognition, reading simple words, and constructing short sentences. Although minor errors in pronunciation and word structure persisted, the subject’s consistent progress throughout the intervention confirmed the phonic method as an effective and applicable approach to teaching reading to slow learners. In conclusion, the phonic method successfully addressed phonological barriers through strategies tailored to the learner’s cognitive profile. The novelty of this study lies in its implementation of the phonic method as a step-by-step phonological intervention model within the context of inclusive primary education an area that remains underexplored and underutilized in both educational practice and research in Indonesia.